Cellulose diacetate composite material with excellent comprehensive performance and preparation method thereof

By combining cellulose diacetate with triethyl citrate and functionally modified Elosite nanotubes, a composite material with excellent comprehensive performance was prepared, which solved the problem of insufficient performance of existing cellulose diacetate materials, and improved performance such as mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antioxidant activity and ammonia-sensitive discoloration, which is suitable for applications in a variety of fields.

CN119735862APending Publication Date: 2025-04-01GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411956706.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing cellulose diacetate materials have insufficient mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antioxidant activity and ammonia-sensitive discoloration properties, which limits their application in food packaging, smart materials, antioxidant materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.

Method used

A composite material with excellent comprehensive performance was prepared by combining cellulose diacetate with triethyl citrate and functionally modified Elosite nanotubes. The preparation method of the composite material includes stirring and drying of cellulose diacetate, triethyl citrate and functionally modified Elosite nanotubes under specific ratios and conditions to form a composite material with excellent mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antioxidant activity and ammonia-sensitive discoloration properties.

Benefits of technology

It has achieved significant improvements in the mechanical strength, ductility, hydrophobicity, ultraviolet barrier, antioxidant activity and ammonia-sensitive discoloration properties of cellulose diacetate materials, and is suitable for food packaging, smart materials, antioxidant materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735862A_ABST
    Figure CN119735862A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and particularly relates to a cellulose diacetate composite material with excellent comprehensive performance and a preparation method thereof. The cellulose diacetate composite material with the excellent comprehensive performance is prepared from the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of triethyl citrate and 2 to 8 parts of functionally modified halloysite nanotubes. The cellulose diacetate composite material with excellent comprehensive performance has excellent mechanical strength, ductility, hydrophobicity, ultraviolet barrier property, oxidation resistance, ammonia-sensitive discoloration and other properties and functions, and the preparation process is simple, environment-friendly, low in cost, suitable for large-scale production and wide in application prospect. The method has wide application value in the fields of food packaging, intelligent materials, antioxidant materials, ultraviolet protection, ammonia gas detection, environment monitoring, safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a cellulose diacetate composite material with excellent comprehensive performance and a preparation method thereof. Background Art

[0002] Cellulose diacetate is a synthetic fiber raw material made by acetylating natural cellulose. It has good plasticity, chemical resistance, heat resistance and biodegradability, and is widely used in textiles, plastics, films, coatings and other fields. However, cellulose diacetate has limited mechanical strength, relatively low tensile strength and flexural strength, is hydrophilic, and lacks antioxidant, UV shielding, ammonia response and other properties, which limits the application of cellulose diacetate in food packaging, smart materials, antioxidant materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. At present, most of the research focuses on improving the thermal and mechanical properties of cellulose diacetate composites, but few studies have reported how to simultaneously improve the mechanical strength, ductility, hydrophobicity, UV blocking, antioxidant and ammonia-sensitive discoloration properties and functions of cellulose diacetate materials. Therefore, how to effectively and simultaneously improve the mechanical strength, ductility, hydrophobicity, UV blocking, antioxidant activity and ammonia-sensitive color change properties of cellulose diacetate materials so as to make them suitable for food packaging, smart materials, antioxidant materials, UV protection, ammonia detection, environmental monitoring and safety and other fields is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a cellulose diacetate composite material with excellent comprehensive performance and a preparation method thereof. The cellulose diacetate composite material with excellent comprehensive performance has excellent mechanical strength, ductility, hydrophobicity, ultraviolet blocking, antioxidant activity and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, suitable for scaled-up production, and is suitable for food packaging, smart materials, antioxidant materials, ultraviolet protection, ammonia detection, environmental monitoring and safety and other fields.

[0004] Technical solution of the present invention:

[0005] The present invention provides a cellulose diacetate composite material with excellent comprehensive performance, characterized in that it is composed of the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of a plasticizer, and 2-8 parts of functionally modified halloysite nanotubes;

[0006] The plasticizer is triethyl citrate;

[0007] The preparation method of the functionally modified halloysite nanotubes comprises the following steps:

[0008] (1) Dispersing 50 parts of halloysite nanotubes in 2000 parts of deionized water, stirring at room temperature for 10 minutes, to obtain a uniform halloysite nanotube dispersion for later use;

[0009] (2) taking 13.91 parts of ferrous sulfate heptahydrate, adding it to the halloysite nanotube dispersion obtained in step (1), stirring at room temperature for 60 minutes to obtain a uniform blended solution for later use;

[0010] (3) Take 8.2 parts of 4-hydroxycinnamic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform 4-hydroxycinnamic acid solution for later use;

[0011] (4) Adding the 4-hydroxycinnamic acid solution obtained in step (3) to the mixed solution obtained in step (2), stirring the mixture at room temperature for 20 min, and then centrifuging, washing, and drying in sequence to obtain functionally modified halloysite nanotubes.

[0012] The present invention also provides a method for preparing the above-mentioned cellulose diacetate composite material with excellent comprehensive performance, which is characterized by comprising the following steps:

[0013] (1) Add 100 parts of cellulose diacetate and 5 parts of plasticizer to 2500 parts of acetone, stir at 35°C for 60 minutes to obtain a uniform blend solution for later use;

[0014] (2) dispersing 2-8 parts of functionalized halloysite nanotubes in 500 parts of acetone to obtain a uniform dispersion for later use;

[0015] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 35° C. for 30 min to obtain a uniform film-forming solution for later use;

[0016] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate composite material with excellent comprehensive properties.

[0017] The application of the cellulose diacetate composite material with excellent comprehensive performance is characterized by being used in the fields of food packaging, smart materials, antioxidant materials, ultraviolet protection, ammonia detection, environmental monitoring and safety.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The cellulose diacetate composite material with excellent comprehensive performance prepared by the present invention has excellent mechanical strength, ductility, hydrophobicity, UV blocking, antioxidant activity and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antioxidant materials, UV protection, ammonia detection, environmental monitoring and safety and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 (a) is a scanning electron microscope image of halloysite nanotubes. Figure 1 (b) is a scanning electron microscope image of the functionally modified halloysite nanotubes involved in the present invention;

[0021] Figure 2 The following are actual photos of the cellulose diacetate composite material samples with excellent comprehensive performance prepared in Comparative Example 1 and the cellulose diacetate composite material samples prepared in Example. DETAILED DESCRIPTION

[0022] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above content of the present invention. The parts of the raw materials are all parts by weight unless otherwise specified.

[0023] In the following specific examples and comparative examples, the cellulose diacetate used is a product provided by Shanghai Yuanye Biotechnology Co., Ltd. (CAS No.: 9035-69-2); the halloysite nanotubes used are high-purity products provided by Guangzhou Runwo Materials Technology Co., Ltd. (see the scanning electron microscope image of the product). Figure 1 (a)); 4-Hydroxycinnamic acid was provided by Shanghai Bid Pharmaceutical Technology Co., Ltd. as an analytically pure reagent; triethyl citrate was provided by Shanghai Yuanye Biotechnology Co., Ltd. as an analytically pure reagent; ferrous sulfate heptahydrate was provided by Xilong Scientific Co., Ltd. as an analytically pure reagent.

[0024] In the following specific examples and comparative examples, the formulations and preparation methods, the functionalized modified halloysite nanotubes (see the scanning electron microscope image of the Figure 1 (b)), the preparation method of which comprises the following steps:

[0025] (1) Dispersing 50 parts of nano-halloysite in 2000 parts of deionized water, stirring at room temperature for 10 minutes, to obtain a uniform halloysite dispersion for later use;

[0026] (2) taking 13.91 parts of ferrous sulfate heptahydrate, adding it to the halloysite dispersion obtained in step (1), stirring at room temperature for 60 minutes to obtain a uniform blended solution for later use;

[0027] (3) Take 8.2 parts of 4-hydroxycinnamic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform 4-hydroxycinnamic acid solution for later use;

[0028] (4) Adding the 4-hydroxycinnamic acid solution obtained in step (3) to the mixed solution obtained in step (2), stirring the mixture at room temperature for 20 min, and then centrifuging, washing, and drying in sequence to obtain functionally modified halloysite nanotubes.

[0029] Example 1

[0030] A cellulose diacetate composite material with excellent comprehensive performance, characterized in that it consists of the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of triethyl citrate, and 2 parts of functionally modified halloysite nanotubes.

[0031] The preparation method comprises the following steps:

[0032] (1) Add 100 parts of cellulose diacetate and 5 parts of triethyl citrate to 2500 parts of acetone, stir at 35°C for 60 min to obtain a uniform blend solution for later use;

[0033] (2) dispersing 2 parts of functionalized halloysite nanotubes in 500 parts of acetone to obtain a uniform dispersion for later use;

[0034] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 35° C. for 30 min to obtain a uniform film-forming solution for later use;

[0035] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate composite material with excellent comprehensive properties.

[0036] Example 2

[0037] A cellulose diacetate composite material with excellent comprehensive performance, characterized in that it consists of the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of triethyl citrate, and 5 parts of functionally modified halloysite nanotubes.

[0038] The preparation method comprises the following steps:

[0039] (1) Add 100 parts of cellulose diacetate and 5 parts of triethyl citrate to 2500 parts of acetone, stir at 35°C for 60 min to obtain a uniform blend solution for later use;

[0040] (2) dispersing 5 parts of functionalized halloysite nanotubes in 500 parts of acetone to obtain a uniform dispersion for later use;

[0041] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 35°C for 30 min to obtain a uniform film-forming solution for later use;

[0042] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate composite material with excellent comprehensive properties.

[0043] Example 3

[0044] A cellulose diacetate composite material with excellent comprehensive performance, characterized in that it consists of the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of triethyl citrate, and 8 parts of functionalized modified halloysite nanotubes.

[0045] The preparation method comprises the following steps:

[0046] (1) Add 100 parts of cellulose diacetate and 5 parts of triethyl citrate to 2500 parts of acetone, stir at 50°C for 60 min to obtain a uniform blend solution for later use;

[0047] (2) dispersing 8 parts of functionalized halloysite nanotubes in 500 parts of acetone to obtain a uniform dispersion for later use;

[0048] (3) Add the dispersion obtained in step (2) to the blended solution obtained in step (1), and stir at 35° C. for 30 min to obtain a uniform film-forming solution for later use;

[0049] (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate composite material with excellent comprehensive properties.

[0050] Comparative Example

[0051] As a comparison standard of the above embodiments, the present invention provides a cellulose diacetate material prepared without functionally modified halloysite nanotubes, comprising the following steps:

[0052] (1) Add 100 parts of cellulose diacetate and 5 parts of triethyl citrate to 2500 parts of acetone, stir at 35°C for 60 min to obtain a uniform blend solution for later use;

[0053] (2) Add 500 parts of acetone to the blended solution obtained in step (1), and stir at 35° C. for 30 min to obtain a uniform film-forming solution for later use;

[0054] (3) The film-forming solution obtained in step (2) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate material.

[0055] Structure and performance test:

[0056] The cellulose diacetate material prepared in the above comparative example and the cellulose diacetate composite material with excellent comprehensive performance prepared in the example were subjected to performance tests, wherein the UV-visible performance was tested by using a UV-visible spectrometer, and the average UV transmittance was calculated with reference to GB / T 18830-2009; hydrophobicity characterization: the water contact angle of the sample material was measured by using a static contact angle tester; the tensile performance was tested by using an electronic tensile testing machine (LDW-2G); the ammonia response test method was as follows: the sample material was exposed to an ammonia environment for 15 minutes, the color change of the sample material was observed and recorded, and the color difference value ∆E of the sample material before and after the ammonia response was calculated (Note: ∆E >3 indicates an obvious color change visible to the human eye).

[0057] The DPPH free radical scavenging experimental method is as follows: for the experimental group, 0.2 g of the sample material was cut into pieces and soaked in 5 mL of ethanol. After soaking for 24 h, 2 mL of the supernatant of the soaking solution was extracted and set aside; then, 1 mL of 50 mg / L DPPH solution was added to the 2 mL of the supernatant, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured using an ultraviolet spectrophotometer. sample ); for the control group, 1 mL of 50 mg / L DPPH solution was added to 2 mL of ethanol, and the mixture was shaken and placed in the dark at room temperature for 1 h; then, the absorbance of the mixture at 517 nm (denoted as A) was measured by a UV spectrophotometer. control );DPPH free radical scavenging rate (%)=100*(A control -A sample ) / A control .

[0058] The above performance test data is shown in Table 1.

[0059] Table 1 Sample performance test data

[0060]

[0061] The results of the ammonia response test experiment show that the cellulose diacetate material prepared in the comparative example is colorless and transparent. After being exposed to an ammonia environment for 15 minutes, its color does not change, and it still exhibits colorless and transparent optical properties, and its ∆E value is 0.26 (that is, the color difference is negligible and cannot be distinguished by the human eye). The cellulose diacetate composite material with excellent comprehensive performance prepared in Example 3 is light yellow. After being exposed to an ammonia environment for 15 minutes, its color changes significantly (from light yellow to brown), and its ∆E value is as high as 31.9 (Note: ∆E >3 indicates a significant color change visible to the human eye).

[0062] The results of the DPPH free radical scavenging experiment show that the cellulose diacetate material prepared in the comparative example has no obvious antioxidant activity, while the cellulose diacetate composite material with excellent comprehensive performance prepared in Example 3 has a DPPH free radical scavenging rate of 79.4%, that is, the cellulose diacetate composite material with excellent comprehensive performance prepared in Example 3 has excellent antioxidant activity.

[0063] In summary, it can be seen from the sample performance test data (see Table 1) that the cellulose diacetate composite material with excellent comprehensive performance prepared by the present invention has excellent mechanical strength, tensile elongation at break (i.e., ductility), hydrophobicity, UV blocking, antioxidant activity and ammonia-sensitive color change and other properties and functions, and its preparation process is simple, environmentally friendly, low-cost, and suitable for large-scale production. It has wide application value in food packaging, smart materials, antioxidant materials, UV protection, ammonia detection, environmental monitoring and safety and other fields.

[0064] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.

Claims

1. A cellulose diacetate composite material with excellent comprehensive performance, characterized in that: The invention is composed of the following components in parts by weight: 100 parts of cellulose diacetate, 5 parts of plasticizer, and 2-8 parts of functionalized halloysite nanotubes; The plasticizer is triethyl citrate; The preparation method of the functionally modified halloysite nanotubes comprises the following steps: (1) Dispersing 50 parts of halloysite nanotubes in 2000 parts of deionized water, stirring at room temperature for 10 minutes, to obtain a uniform halloysite nanotube dispersion for later use; (2) taking 13.91 parts of ferrous sulfate heptahydrate, adding it to the halloysite nanotube dispersion obtained in step (1), stirring at room temperature for 60 minutes to obtain a uniform blended solution for later use; (3) Take 8.2 parts of 4-hydroxycinnamic acid, dissolve it in 5000 parts of ethanol, and stir at room temperature for 10 minutes to obtain a uniform 4-hydroxycinnamic acid solution for later use; (4) Adding the 4-hydroxycinnamic acid solution obtained in step (3) to the mixed solution obtained in step (2), stirring the mixture at room temperature for 20 min, and then centrifuging, washing, and drying in sequence to obtain functionally modified halloysite nanotubes.

2. The method for preparing a cellulose diacetate composite material with excellent comprehensive performance according to claim 1, characterized in that The steps include: (1) Add 100 parts of cellulose diacetate and 5 parts of plasticizer to 2500 parts of acetone, stir at 35°C for 60 min to obtain a uniform blend solution for later use; (2) dispersing 2-8 parts of functionalized halloysite nanotubes in 500 parts of acetone to obtain a uniform dispersion for later use; (3) adding the dispersion obtained in step (2) to the blended solution obtained in step (1), stirring at 35° C. for 30 min to obtain a uniform film-forming solution for later use; (4) The film-forming liquid obtained in step (3) is poured into a flat-bottomed dish and dried in an oven at 55° C. for 24 h to obtain a cellulose diacetate composite material with excellent comprehensive properties.

3. The use of a cellulose diacetate composite material with excellent comprehensive performance according to claim 1, characterized in that: Used in food packaging, smart materials, antibacterial materials, UV protection, ammonia detection, environmental monitoring and safety fields.

Citation Information

Cited By

  • Preparation method and use method of 3D printed crystal violet lactone temperature monitoring label

    CN121740274A

  • A method of making and using a 3D printed crystal violet lactone temperature monitoring label

    CN121740274B